PEMENUHAN KEBUTUHAN SPIRITUAL CARE PASIEN RAWAT INAP - Mardiani, Mardiani (JURNAL MEDIA KESEHATAN, 2017)
Nurses who have the ability to identify and understand the spiritual aspects of thepatient, will be able to carry out spiritual fulfillment and knowing how spiritual beliefs can affectthe life of every individual. The purpose of this research is the perception of nurses correlationwith the fulfillment of the spiritual care of patients in inpatient hospitals Dr.M. YunusBengkulu. The type of this research is analityc with cross sectional design. The Researchsample is nurses inpatient ward of RSUD Dr. M. Yunus Bengkulu who numbered 83 nursestaken with total sampling technique. Research done at eight wards hospitals Dr. M YunusBengkulu for two months. Collecting data using a questionnaire. Quantitative data analysis isunivariate and bivariate with uji chi-square at α 5%. The results showed that there was a significantrelationship between the perception of nurses and spiritual fulfillment of inpatientcare in hospitals Dr.M.Yunus Bengkulu (p : 0.022) with OR 3.107 (95% CI : 1.265 to 7.630),which means nurses have perceptionless chance three times to apply the spiritual care that isless favorable than that good perception. To the Hospital Dr. M. Yunus Bengkulu expectedfor the provision of facilities and additional skills for nurses in the inpatient room about theimportance of spiritual fulfillment as well as the necessary care program to improve the perceptionof nursing care, especially for spiritual fulfillment inpatients.